The Use of MiniMed780G System Is Associated With Stable Glycemic Control in People With Type 1 Diabetes Before, During, and After Ramadan: An Observational Study - Abdullah M. Alguwaihes; Najla Alotaibi; Metib Alotaibi; Naglaa Masry; Saher Safarini (Journal of Diabetes Research, 2025)
Conclusion: The use of the MiniMed780G system is safe with favorable glycemic outcomes across nonfasting and fasting months.